The pH of bottled water commercially available in Australia and its implications for oral health. (26th April 2022) - Schmidt, Jeremiah; Huang, Boyen
Abstract: With a higher pH level and being unlikely to erode the tooth, bottled water has been considered a safe alternative to acidic beverages. However, recent studies have reported some bottled water products in different countries to be acidic. The present paper aimed to examine the pH values of 42 bottled waters commercially available in Australia, using a pH meter and probe, and classify their risks to cause erosive tooth wear in comparison with the critical pH of enamel and dentine. Of the 42 bottled water samples collected, 81.0 and 73.8% were considered erosive to tooth dentine and enamel, respectively. Flavoured waters were the most acidic, followed by sparkling waters, spring waters, artesian waters, mineral waters, and alkaline waters. All sparkling waters and flavoured waters showed an erosive risk to the enamel and dentine. A portion of spring waters and artesian waters was also acidic enough to erode tooth structures. The findings of this work were of concern given the risk of sustaining erosive tooth wear from consuming bottled waters. Health promotion strategies including public awareness and education on oral health consequences related to the consumption of bottled water are needed. Future epidemiological and in vivo investigations are also warranted. HIGHLIGHTS: The majority of bottled waters sold in Australia could result in erosive tooth wear. Flavoured waters were the most acidic bottled water products. Awareness and knowledge of oral health consequences related to bottled water consumption is relevant. Graphical Abstract